Gozdni požar na Potoški gori in sanacija v požaru poškodovanih gozdov - Rozman, Jurij (Gozdarski vestnik, 2024)
Forest fires are becoming ever more frequent and intense due to climate changes and human activities, where the mountain areas are especially vulnerable. The consequences of fires are more severe since difficult access and steep terrain cause faster spread of fire and more demand putting it out. A particular case is the fire on Potoška Gora in 2022, causing big ecological and economic damage. The experiences show we need a well-planned forest structure enabling the transport of firefighters and technology, arial support for firefighting, and the vicinity of appropriate water sources for successful fire control on mountain terrains. The rehabilitation of the affected áreas incorporates prevention of soil erosion, felling of the damaged trees, and limited target regeneration by planting and seeding. Fires on the steep slopes create new ecological niches; however, they also cause numerous challenges, like problems in the natural regeneration due to the absence of seed trees, exposure to erosion and weather, grazing by game, and lessened owners' motivation for cooperation in the regeneration. Harmonized activities of foresters, forest owners, environmentalists, and the local community are essential for ensuring a successful regeneration of forest ecosystems. Adapting forest management plans and introducing effective preventive measures, including consideration of the fire protection role of forest roads and other infrastructure elements, are crucial for reducing the risk of future fires. Also, directing recreation in the natural environment and making society aware of the danger of fires, prevailingly caused by people, are essential.
Keywords: fire site restoration; forest fires; forest rehabilitation after fire; gorski svet; gozdni požari; mountain world; obnova požarišča; Potoška gora; rehabilitation plan; sanacija gozdov po požaru; sanacijski načrt